2020
DOI: 10.3934/eect.2020011
|View full text |Cite
|
Sign up to set email alerts
|

Null-controllability properties of a fractional wave equation with a memory term

Abstract: We study the null-controllability properties of a one-dimensional wave equation with memory associated with the fractional Laplace operator. The goal is not only to drive the displacement and the velocity to rest at some time-instant but also to require the memory term to vanish at the same time, ensuring that the whole process reaches the equilibrium. The problem being equivalent to a coupled nonlocal PDE-ODE system, in which the ODE component has zero velocity of propagation, we are required to use a moving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Nevertheless, in recent years, several results have been obtained on the controllability properties of hyperbolic (wave) and dispersive (Schrödinger) models involving the fractional Laplacian. The interested reader may refer, for instance, to [12,18,92]. As for the numerical approximation of wave-type models, this issue is known to be quite delicate.…”
Section: Conclusion and Open Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, in recent years, several results have been obtained on the controllability properties of hyperbolic (wave) and dispersive (Schrödinger) models involving the fractional Laplacian. The interested reader may refer, for instance, to [12,18,92]. As for the numerical approximation of wave-type models, this issue is known to be quite delicate.…”
Section: Conclusion and Open Problemsmentioning
confidence: 99%
“…In recent years, this class of models has got the attention of the control community (see for instance [17,33,66] or [18] for models involving the fractional Laplacian). In particular, it has been observed that these models can be cast as coupled PDE-ODE systems, in which the ODE component introduces non-propagation effects similar to those produced by a low-order (s ≤ 1/2) fractional Laplacian.…”
Section: Conclusion and Open Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research on fractional Laplace operators and their applications is very attractive and extended. In the last decade, many authors from different fields of the pure and applied mathematics have considered PDE models involving the fractional Laplacian and addressed many relevant questions such as existence, uniqueness and regularity of solutions [5,10,13,14,15,17,31,32,34,39,40,41,47,48,49,50], spectral properties [22,23,28], or even more applied issues, for example control problems [8,9,11,12,42,43,44,45] or the description of several phenomena arising in finance and quantum mechanics [4,14,27].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning wave-like models, the approximate controllability from the exterior of fractional wave equations has been proved in [35,57], while [6] treats the null-controllability of a one-dimensional fractional wave equation with memory. Nonetheless, as far as the author knows, there are currently no controllability results for the fractional Schrödinger equation.…”
mentioning
confidence: 99%